Colorenal Fistula after Renal Tumour Cryotherapy: A Case Report - Sorabilla, Andoni Alaba; Rodríguez, Julia Pelayo; Lázaro-Carrasco, Oihan Loidi; González, Rubén Gonzalo; Ruiz, Ruben Caiña; Rivas, Berta Martín; Cabezas, José Manuel Gutiérrez (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Introduction: The incidence of renal cell carcinoma has been increasing in recent years. The primary techniques for the treatment of these tumours are cryoablation, radiofrequency ablation, percutaneous ethanol injection, and microwave ablation. Computed tomography (CT)-guided percutaneous cryoablation is increasingly utilized for renal cell carcinoma. Bowel injury is a known complication but is extremely rare. This study presents a rare case of colorenal fistula after cryoablation of a left renal tumour. Presentation of Case: A 58-year-old man with no significant history was diagnosed with left renal carcinoma A left renal tumour was incidentally found on an abdominal CT examination performed for a slight increase in transaminases. Abdominal ultrasonography revealed a 31 × 32-mm solid, well-defined, cortical tumour at the lower pole of his left kidney. The patient was asymptomatic and had no distant metastasis. The decision was made to treat the tumour with percutaneous cryoablation, with a good response to the technique. Two months later, the patient had recurrent urinary tract infections and pneumaturia. In the absence of improvement with antibiotic treatment, CT was performed and revealed a fistula connecting the descending colon and renal parenchyma. The decision was made to perform surgery to repair the defect caused by percutaneous cryotherapy. The patient recovered from surgery and was discharged with no complications. Discussion: To reduce the adverse effects of radical or partial nephrectomy and preserve renal function, percutaneous ablation techniques have been developed. Internal injury is a known complication and it is particularly common in cases of renal tumours located in the upper and anterior kidney. The diagnosis is based on symptoms and imaging. Most colorenal fistulas have been treated conservatively with good results. Conclusion: Cryoablation of renal tumours is a safe, low-risk procedure, but recurrent urinary tract infections and pneumaturia may indicate a colorenal fistula, with conservative treatment preferred and surgery reserved for persistent cases. If possible, conservative medical treatment should be used, reserving surgery for complicated or persistent colorenal fistulas.